Factors That Drive Consumers In Purchasing Decisions For Macbook Air Brand Laptops In Banda Aceh City - Rizal, Syamsul; Tarmizi; Alfina (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Nowadays, laptops are no longer a rare item, where more and more consumers can afford laptops, but the higher a person's income, the more their lifestyle will improve. A laptop is a tool that can make a person's work easier in all fields. Laptops are known as computers that can be carried anywhere. So it attracts many consumers. The purpose of this research is to determine the factors that encourage consumers to purchase Macbook Air Brand Lantops in Banda Aceh City and try to provide suggestions that are deemed necessary to improve and increase sales volume based on management theories and things that arises in other discussions. The writer collected information from respondents from the columnists who bought Macbook Air Brand Laptops in Banda Aceh City. The author distributed a questionnaire containing various statements with fields to be filled in by respondents. The entry column is designed using a Likert scale technique with 8 categories as shown below. With a sample size of 100 respondents. Based on the research results, psychological factors (x1), socio-cultural factors (x2), marketing mix factors (x3) and macro environmental factors (x4) all have an influence in increasing laptop purchasing decisions in the city of Banda Aceh, namely by obtaining a calculated F value of 49.514, and Ftable at the significance level ∞ = 5% is 2.311 with a significance level of 0.000. This states that simultaneously (together) the indicator variables used in this research model influence the decision to purchase laptops in Banda Aceh City.